An economically efficiently structuring procurement processes state (2015)
The structuring of contractual processes is a complex issue, but approach it becomes interesting since all its components are determined by law. There are a variety of documents relating to the subject, but the best way to handle it is generating a diagram that leads to step of the process itself, a way to guide those involved in the contractual process and enable them to learn in a practical way as it is the cycle and what are the procedures at each step within the same, applying the provisions of the standard.